Doing Human Service Ethnography - Jacobsson, Katarina; Gubrium, Jaber F. (Policy Press, 2021)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Human service work is performed in many places – hospitals, shelters, households, prisons, schools, clinics – and is characterised by a complex mixture of organising principles, relations and rules. Using ethnographic methods, researchers can investigate these site-specific complexities, providing multi-dimensional and compelling analyses. Bringing together both theoretical and practical material, this book shows researchers how ethnography can be carried out within human service settings. It provides an invaluable guide on how to apply ethnographic creativeness and offers a more humanistic and context-sensitive approach in the field of health and social care to generating valid knowledge about today’s service work.